2018
DOI: 10.1037/pro0000206
|View full text |Cite
|
Sign up to set email alerts
|

Clues from the digital world: A survey of clinicians’ reliance on social media as collateral data in forensic evaluations.

Abstract: Access to and use of social media has increased throughout the United States. In parallel, information gleaned from social media is often available as part of discovery packets provided to clinicians conducting forensic evaluations. As social media continues to be a primary mode of communication, forensic evaluators are likely to grapple with decisions to use information from these sites to inform psycholegal opinions. However, professional commentary on obtaining, interpreting, and integrating data from socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…[ 32 ]. The data provided from social media is more understandable and easy to access for users [ 33 , 34 , 35 ]. To use this type of data, it is required to follow the legal and formal process [ 36 ].…”
Section: Related Workmentioning
confidence: 99%
“…[ 32 ]. The data provided from social media is more understandable and easy to access for users [ 33 , 34 , 35 ]. To use this type of data, it is required to follow the legal and formal process [ 36 ].…”
Section: Related Workmentioning
confidence: 99%
“…Because history is paramount, the understanding of the individual defendant should be informed on the case investigative level. Full access to the smartphone of the defendant and other related actors, for example, provides abundant, critically relevant and valid contemporaneous data uncorrupted by adversarial positioning and is the most diagnostic source material available to emotional, cognitive, and behavioral understanding today (Coffey et al, 2018).…”
Section: Criminal Maturity and Homicidementioning
confidence: 99%
“…Although forensic mental health scholars have begun to discuss the risks and benefits of Internet-derived data (see Batastini & Vitacco, 2020), there has been little empirical investigation into the matter. In a survey of 102 forensic evaluators, 63.7% reported using social media as collateral information, most often in mental state and child custody evaluations (Coffey et al, 2018). In general, evaluators reported that social media information was not as helpful in developing their forensic opinion as were hospital and police records, clinical interview, surveillance tapes, support staff, and family members.…”
Section: Review: Components Of Forensic E-mental Healthmentioning
confidence: 99%